2009
DOI: 10.17221/672-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactococcus sp. on the growth of Listeria sp. in the model UHT milk system

Abstract: Abstract:The work was aimed at the growth suppression of cultured listerias strains by cultured lactococci strains or commercial mesophilic cheese cultures during common cultivations in the model UHT milk system (0.5% w/w of milk fat content) at 30°C during 18 h aerobically. Milk was primarily fermented by lactococci at the level of 10 8 CFU/ml and secondarily contaminated by listerias at the level of 10 3 CFU/ml. The most intensive growth suppressions of both Listeria innocua (CCM 5884 or Ln-03) strains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…mundtii CCM 1282) were chosen for this study because of their significant potential for the application in fermented dairy technology as biopreservative agents. The antilisterial activity of these strains against non-pathogenic L. innocua, commonly used as indicator strain, was previously confirmed (Kučerová et al 2009;Šviráková et al 2009 (Liu & Hansen 1990) and known as thermostable (Hurst 1981), was not confirmed as the main antilisterial agent for CCDM 416, as was primarily assumed. Probably, the production of another unspecified thermolabile compound is expected.…”
Section: Resultsmentioning
confidence: 98%
“…mundtii CCM 1282) were chosen for this study because of their significant potential for the application in fermented dairy technology as biopreservative agents. The antilisterial activity of these strains against non-pathogenic L. innocua, commonly used as indicator strain, was previously confirmed (Kučerová et al 2009;Šviráková et al 2009 (Liu & Hansen 1990) and known as thermostable (Hurst 1981), was not confirmed as the main antilisterial agent for CCDM 416, as was primarily assumed. Probably, the production of another unspecified thermolabile compound is expected.…”
Section: Resultsmentioning
confidence: 98%
“…The antilisterial effect ( L. monocytogenes reductions of 3–4 log10 units in cheese) of the added bacteriocinogenic of L. lactis spp. lactis provides an important biological control potential in cheese production, as evidenced by numerous authors (Šviráková et al ., 2009). The results suggested the potential of using lactococci in cheese production, as part of the mesophilic starter cultures contributing to the biological system of effective control of L. monocytogenes growth.…”
Section: Resultsmentioning
confidence: 99%